International Higher Education's ScholarPractitioners: Bridging Research and Practice - Adhikari, Soni (Journal of International Students, 2017)
In response to dynamics like the above, readers expect international higher education research and scholarship to be situated in the broader global context and address geopolitical dynamics on transnational scales. Unfortunately, in the United States, scholarly responses to changing global dynamics are usually slow and weak. The convention here is for scholars to discuss “internationalization” in the abstract without situating national discourses in the international context or using transnational perspectives.